Poverty and Conflict: Causal Factors and Resolutions - Kartika Bintarsari, Nuriyeni; Tri Utami, Arum (KnE Social Sciences, 2023)
The article examines the relationship between poverty and conflict. Violent conflicts will likely occur in developing countries or regions, such as Sub-Saharan Africa, Africa, Eastern Europe, or Southeast Asia. The main question is whether they are caused by extreme poverty, so there is a scarcity of resources that leads to violent conflicts, or whether there are enough resources. However, only a handful of people in that society can access the resources, which in the end, creates friction and conflict. The conflict has multifaceted dimensions; usually, there is no single cause of conflict. Instead, it involves many aspects, such as political, social, economic, cultural, and other conditions. Economic disparities, gender inequality, unequal distribution of power, power struggles within different societies, climate crises, ethical tensions, genocides, and many other reasons may serve as the causes of conflict. This article will analyze the two factors likely to cause conflict, greed and grievance. Greed and grievance are seen in the case studies presented in this article - the civil war in the aftermath of the Cold war period, which occurred in the 1990s. Keywords: Conflict, Greed, Poverty, Civil Wars